The effect of skiing intensity on shooting performance in biathlon - Vonheim, A. (Norwegian University of Science and Technology, 2012)
An earlier study of shooting performance in biathletes found a decrease in performance as the intensity increased. No studies have focused on the technique used by biathletes in standing shooting, which differs from the technique used by rifle shooters. Therefore, the present study investigated both shooting performance at different exercise intensities in biathletes, and the difference between isometric and dynamic precision at different intensities. To investigate shooting performance at different intensities, 15 biathletes performed three roller ski interval exercises (4x6 min) on a treadmill at 75-80%, 85-87% and 90-95% of their maximum heart rate (HRmax). The biathletes performed 3 precision tasks at rest before warm up, directly after warm up and after each repetition on the interval exercises. The following precision tasks were performed (in standing position): 5 shot series, holding still at a target (isometric), and following a line (dynamic). During the precision tasks, the subjects were standing on a force plate that measured center of pressure (COP) movements in the anterior-posterior direction and medial-lateral direction. Subjects used their own weapon in the precision tasks. A laser pen and an accelerometer were attached at the front of the barrel. The "front sight" was removed from the weapon, and subjects used only their rear sight and the laser dot for aiming. The results showed no significant effect of intensity on shooting performance during the 5 shot series (p= 0.179). The holding still task and following line task were both significant affected by intensity (holding still p= 0.017, following line p= 0.030), but the difference between the two tasks did not reach statistical significance (p= 0.070). Results from the force plate showed greater movement of COP in the anterior-posterior direction than in the medial-lateral direction. A significant effect of intensity was only found in the medial-lateral direction. In conclusion, the present study shows no significant effect of intensity on the shooting performance in the 5 shot series. The subjects were not used to having a laser pen for aiming, and this may have affected the results. There is a difference between isometric and dynamic precision, but the difference did not reach statistical significance. Thus, the results cannot for certain justify the technique used by biathletes in standing position.